Feasibility of Gateway-Less IoT E-Health Applications - Pereira, Carlos (2018)
Machine-to-Machine (M2M) communications are a key enabler of Internet of Things (IoT) applications. One domain with growing interest in M2M/IoT is e-health, either for self-monitoring, home monitoring, or hospital systems. However, current sensing devices in this domain rely on short-range communication protocols that require a gateway (GW) for Internet connection. Smartphones have been proposed as GWs in mobile M2M communications due to their enhanced connectivity and sensing capabilities. However, the GW functionality impacts on the smartphone usability, causing undesirable battery depletion and the smartphone itself increases the overall cost of e- health solutions. In this work, we propose converging e-health devices and Wi-Fi towards direct Internet access through the existing Wi-Fi infrastructure and by-passing current GWs. We use recent low-cost ultra low-power Wi-Fi modules and feature them with M2M capabilities supporting their integration in an interoperable e-health framework. We present results on end-to-end latency and power requirements within a concrete e-health use case that show the feasibility of the proposed GW-less solution.